Pengaruh Organizational Citizenship Behavior, Efikasi Diri, dan Soft Skills Terhadap Kinerja Karyawan - Myrza Latifah; Qristin Violinda; Noventia Karina Putri (Green Economics Review, 2024)
This research aims to determine the influence of Organizational Citizenship Behavior, Self-Efficacy, and Soft Skills which simultaneously have a positive effect on the performance of PGRI University Semarang employees. This research uses a quantitative approach with data analysis techniques using descriptive statistics. The population in this research is employees of PGRI University Semarang, the sample used is 57 people. Organizational Citizenship Behavior (X1) partially has no effect on the performance of PGRI Semarang University employees. This can be proven by the t calculated results on the Organizational Citizenship Behavior (X1) variable of 1.012, thus the t calculated is smaller than the t table (1.012 < 2.397) and the significant value is > 0.05. So it can be concluded that Ho is accepted and Ha is rejected, which means that Organizational Citizenship Behavior (X1) has no significant effect on employee performance (Y). Self-Efficacy (X2) partially influences the performance of PGRI Semarang University employees. This can be proven by the t calculated results on the Self Efficacy variable (X2) of 5.724, thus the t calculated is smaller than the t table (5.724 > 2.397) and the significant value is < 0.05. So it can be concluded that Ho is rejected and Ha is accepted, which means that Self-Efficacy (X2) has a significant effect on employee performance (Y). Soft Skills (X3) partially influence the performance of PGRI University Semarang employees. This can be proven by the calculated t result on the Soft Skill variable (X3) of 9.439, thus the calculated t is smaller than the t table (9.439 > 2.397) and the significant value is <0.05. So it can be concluded that Ho is rejected and Ha is accepted, which means Soft Skill (X3) has a significant effect on employee performance (Y). Organizational Citizenship Behavior (X1), Self-Efficacy (X2) and Soft Skills (X3) simultaneously (together) influence Employee Performance (Y). This can be seen from the calculated F test results which obtained a significance value of 393.684 and a significance value of 0.000 <0.05. So it can be concluded that Ho is rejected and Ha is accepted, which means that the variables Organizational Citizenship Behavior (X1), Self-Efficacy (X2) and Soft Skills (X3) have a significant effect on Employee Performance (Y).